Menangani Relaps Dengan Teknik Terapi Tingkah Laku Dan Kognitif (Cbt) - Amin Al Haadi Shafie; Nurul Ashikin Miskam; Azad Athahiri Bin Anuar; Norsayyidatina Bt Che Rozudi; Wan Ahmad Zakry B. Wan Kamaruddin; Musa B. Mohamad (Universiti Sains Islam Malaysia, 2024)
Drug abuse has been declared as the number one enemy of the country since 1983. Various efforts have been conducted by the government to help address the problems of drug abuse. The increasing number of drug addicts is not only due to the number of new drug addicts, but also relapse cases. Relapse is caused by 'Triggers' in which the addict feels 'Craving' for drugs. 'Trigger' can be: (1) people, (2) place, (3) situation and (4) drugs itself. There are techniques to help in address the problem of relapse according to the cognitive behavior Therapy. This technique is called 'Relapse Prevention Techniques' (RP) which involving seven (7) steps. The Seven steps are: (1) Identify the level of motivation of the clients, (2) Identify risk situations, (3) change the lifestyle, (4) Identify the client’s process of relapse, (5) identify when the clients made irrelevant decisions (6)Identify cognitive factors related to relapse and (7) Management of risk situations.